2016
DOI: 10.1111/jam.13178
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro activity of carbapenems against clinical isolates of Acinetobacter baumannii

Abstract: Doripenem should be considered as a therapeutic option for monotherapy or combination therapy, particularly when the therapeutic options are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Finally, doripenem was comparable to other carbapenems, including imipenem and meropenem, in terms of microbiological eradication rate in the subgroup analysis. All these findings may be well explained by previous in vitro studies [3,4,19,20,21] that showed doripenem had a greater or similar in vitro activity against bacteria, including multi-drug resistant organisms. In this meta-analysis, we did not assess we did not evaluate the association between in vitro activity and the in vivo response of different organisms, especially for antibiotic-resistant pathogens, because the associated information was limited.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Finally, doripenem was comparable to other carbapenems, including imipenem and meropenem, in terms of microbiological eradication rate in the subgroup analysis. All these findings may be well explained by previous in vitro studies [3,4,19,20,21] that showed doripenem had a greater or similar in vitro activity against bacteria, including multi-drug resistant organisms. In this meta-analysis, we did not assess we did not evaluate the association between in vitro activity and the in vivo response of different organisms, especially for antibiotic-resistant pathogens, because the associated information was limited.…”
Section: Discussionsupporting
confidence: 53%
“…Carbapenems, including imipenem and meropenem, remain the mainstay of treatment for hospital-acquired infections, especially for the multidrug-resistant organism associated infections [1]. Doripenem is another important carbapenem, and has excellent bactericidal activity against most nosocomial pathogens according to several in vitro studies [2,3,4,5]. A global surveillance showed that doripenem was at least two-fold more potent in in vitro activities than imipenem and meropenem against Pseudomonas aeruginosa —an important nosocomial pathogen [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening of resistance to a carbapenem according to the disk diffusion method was common among the studies. 8 – 23 Although this method may be applicable for many antimicrobials, however, for carbapenems more confirmatory tests beyond the disk diffusion assay are needed. In this setting, MIC would help for detection of resistant isolates.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were multicenter, 8 – 12 but the sample sizes for three of them were small. 10 , 13 , 14 The trend of resistance to a carbapenem did not follow a specific pattern.…”
Section: Resultsmentioning
confidence: 99%